Insights into general practitioners’ self-care across 38 countries during the pandemic: a cross-sectional study - Ivana Keenan; Esther Van Poel; Els Clays; Sara Willems; Milena Šantrić Milićević; Katica Tripković; Liubovė Murauskienė; Kathryn Hoffmann; Radost Assenova; Carmen Busneag; Gazmend Bojaj; Claire Collins (BMC Psychology, 2024)
Abstract Background The adoption of healthy self-care practices has proven necessary for professional life, as they often serve as a shield against stressors in the workplace. The COVID-19 pandemic created a high strain on general practitioners (GPs), contributing to increased workload, burnout, and anxiety. The present study aimed to identify self-care practices adopted by GPs amid the COVID-19 pandemic; and to explore the relationships between self-care practices and risk of distress. Methods The current study utilized an online questionnaire arriving from the PRICOV-19 study, which was distributed among GP practices across 38 countries. The main focus was on the open-text responses where participants disclosed self-care practices employed to maintain mental health during COVID-19. The Six Domains of Self-Care theoretical framework was applied to investigate GP self-care practices across 6 domains including Physical, Professional, Relational, Emotional, Psychological, and Spiritual. The Mayo Clinic Well-Being Index (eWBI) was applied to assess mental well-being and risk of distress among GPs. The analysis was carried out using SPSS Statistics software. Results In total, 2,949 GPs provided open-text responses on maintaining their mental health. 65.5% of GPs had an eWBI score of ≥ 2 and were considered at risk of distress. The majority of the participants prioritised physical (61.7%), followed by relational (38.0%) and psychological (34.6%) self-care practices to maintain their mental health during the pandemic. GPs who applied relational, physical, and professional self-care were significantly less likely to experience depression, stress, and emotional exhaustion, in comparison with the ones who did not apply these practices. GPs who practiced professional self-care practices had the lowest distress risk (eWBI = 1.99). Overall, 5% of GPs disclosed not applying any practices to maintain their mental health during the pandemic and were the most prone to mental health distress. Conclusions GPs have navigated the pandemic uniquely, and despite applying self-care practices they faced some level of impact, hence self-care interventions for healthcare professionals should be regarded as essential rather than optional. A long-term investment in strategies focused on improving GPs’ self-care is necessary to increase resilience among GPs and ensure their optimal well-being levels are achieved.